Aplikasi Expert system Pengembangan Karir Menggunakan Inventory Kepribadian Entrepreneurship - Resmi Darni; Dony Novaliendry; Ika Parma Dewi (Ikatan Ahli Informatika Indonesia (IAII), 2020)
This study aims to describe the process of designing expert system applications in career development using entrepreneurship personality inventory. The reason for conducting this research is a) the limited number of instruments that are able to measure the entrepreneurship personality of vocational students, b) the high costs incurred in conducting personality tests in career development of vocational students, c) The need for an application that is able to speed up the process of identifying personality and provide recommendations careers for vocational students. The research methodology used is Research and Development. There are four stages that must be carried out: Define, Design, Develop and Disseminate. The instrument used to measure entrepreneurial personality is inventory (non-test) with four indicators of entrepreneurship personality, namely Extroverted, Leader, Moderate Risk Taker, Ambisious, and tested fit using Confirmatory Factor Analysis. The research sample was 30 vocational high school students in the field of Information Technology and Computers. Bayes Method is used for the process of transferring knowledge from experts to the system and decision making, after Based on the results of data analysis, it was found that a) Career development applications based on Entrepreneurship Personality are valid with a percentage (0.887) and very practical (91.11), the results of product effectiveness are 82.47 (effective). Therefore this application is declared valid, practical and effective in measuring the personality of vocational student entrepreneurship.